IMPLEMENTASI PENGGUNAAN ALOKASI DANA DESA (ADD) DAN DANA DESA (DD) DI DESA MEKARJAYA KECAMATAN CIJAKU KABUPATEN LEBAK - Ihin Solihin Ihin Solihin (LPPM STIA Banten, 2018)
From the results of a study conducted at the office of Mekarjaya Village, Cijaku Sub- District, Lebak District, the management of village finance has not been carried out properly. With the existing keywords, then: to find out actions in implementing the use of village funds based on rules or laws. The results of the utilization of village funds can be enjoyed by the people of Mekarjaya Village, Cijaku District, Lebak Regency. In this study using a type of qualitative research. This research was conducted in the office of Mekarjaya Village, Cijaku District, Lebak Regency. Sources of research data taken from several primary and secondary data relating to the Implementation of the Use of Village Funds and Village Funds in Mekarjaya Village, Cijaku District, Lebak Regency. The results of the study can be concluded that the village financial management has not been carried out properly this is due to the incompatibility that applies in the government of Mekarjaya Village including the authority in the division of tasks not according to their ability